The lungs in renal failure. - Lee, H Y (1975)
Pulmonary function was studied in 55 patients with renal failure and no clinical or radiographic evidence of lung disease. A defect of gas transfer was found to be the rule due to a reduction in the diffusing capacity across the alveolar capillary membrane; this abnormality appeared to be related to the severity of the renal impairment. There was also a restrictive ventilatory defect which was more marked in male than in female patients. The significance of these findings is discussed, and attention is drawn to their relevance for patients receiving immuno-suppressive therapy or renal transplantation, in whom pulmonary complications are relatively common.